EXTERNAL CRAWLING ROBOT FOR FAULT DETECTION IN PIPE - N, Nagarajan; N, Arun kumar; M.D, Shreedharan; M, Jeganathan (International Journal of Psychosocial Rehabilitation, 2018)
The target of the undertaking is to plan a conservative and consistent outer line creeping gadget that helps the assessment of the line in ventures to identify the spillage of gas in the line. The robot is constrained by the remote for its development. The interesting element of the plan of the line crawler is that it can slither in the two ways and stops its creeping when an issue is recognized. The gadget comprise of two rings that are connected to one another along the longitudinal pivot of the line. In the middle of the two rings the agreeable system is put. The consistent system comprise of the tension sensor which detects the air spillage from the line. The agreeable instrument changes the data about spillage in the line to the microcontroller. The microcontroller shows the shortcoming data in the LCD show and alongside the distance where precisely the issue is found from the beginning stage of the robot. One more benefit of the plan is that the robot stops itself toward the finish of the line by the surface sensor and abstain from tumbling down. The PIC 16F877A microcontroller which orders the robot by getting the guidelines from the client through the remote. In view of the order from the client the microcontroller will run the engines in the robot through the driver circuit (ULN 2803). The working of the microcontroller is coded utilizing c language. The robot assists with tracking down the area of the issue in the line and keeps away from spillage and harm in a huge degree. This smaller and agreeable outer line slithering robot will basically go about as a Pipe Inspector.